Tuning the SOCT-ISC of bodipy based photosentizers by introducing different electron donating groups and its application in triplet-triplet-annihilation upconversion. (February 2020) - Liang, Hui; Sun, Shanshan; Zafar, Mahmood; Yuan, Zhanxiang; Dong, Yuye; Ji, Shaomin; Huo, Yanping; Li, Ming-De; Zhao, Jianzhang
Abstract: To study the effect of electron-donating ability on spin orbit charge transfer intersystem crossing (SOCT-ISC) efficiency, a series of bodipy derivatives (BDP-O, BDP-2-MN, BDP-2-EN ) linked with electron-donating groups with different electron-donor abilities were synthesized. For BDP-2-MN and BDP-2-EN, both compounds show a sharp charge transfer emission band at 630 nm, and the local excited (LE) emission in both compounds were completely quenched due to photo-induced electron transfer (PET). By femtosecond transient absorption measurement, the triplet state population in both compounds was confirmed to occur through charge recombination (1996 ps 2307 ps) process after the photo-induced electron transfer upon photoexcitation of bodipy moiety. A long-lived triplet excited state was observed for both compounds (lifetimes: 37 42 μs) via nanosecond transient absorption. The BDP-2-MN and BDP-2-EN can act as the triplet photosensitizers without heavy elements for the application of triplet-triplet-annihilation upconversion (TTA-UC, ΦUC can reach 4.88%). In case of BDP-O molecule, no triplet signal was observed for this compound because of poor electronic coupling between donor and acceptor. Therefore, the triplet excited state properties of bodipy chromophore was successfully regulated by adjusting electronic strength of donor moiety and implement these photosensitizers in the application of TTA-UC. Graphical abstract: Image 1 Highlights: Two triplet photosensitizers BDP-2-MN and BDP-2-EN based SOCT-ISC mechanism were synthesized. The effect of electron-donating ability on SOCT-ISC was studied. BDP-2-MN and BDP-2-EN are successfully used for TTA-UC with efficient upconversion emission.